Analysis of Code Switching Used in Student-Lecturer Interactions in Online Learning Using Whatsapp - Lalu Jaswadi Putera; Nona Arlita Yuningsih; Muhammad Amin (LP2M STIT Palapa Nusantara, 2021)
This study focuses on how code switchings (CS) are used in the student-lecturer interaction in WhatsApp-based online learning. It specifically aims at investigating the types, the functions, and the most dominant types of CS used in the so-called interaction. 233 code-switched utterances from the students’ and the lecturer’s chats were collected as the primary source data. The chats took place during the online learning of the Academic Vocabulary and Corpus course from March to November 2020. For data analysis, the types of CS proposed by Poplack and the functions of CS by Eldridge and Flyman-Mattsson/Burenhut were endorsed. The results show that the analyzed data contain 3 types of code-switching that included tag switching (21 uses, 9%), intra-sentential switching (197 uses, 85%), and inter-sentential switching (15 uses, 6%). Intra-sentential switching is the most dominant type found in the conversation. During the interaction, the lecturer applied 3 functions of CS that included topic switch (46%), affective function (23%), and repetitive function (31%). Meanwhile, the students applied 4 functions of CS that included equivalence (28%), floor-holding (2%), reiteration (52%), and conflict-control (18%).